A Soft Lithiophilic Graphene Aerogel for Stable Lithium Metal Anode. (5th June 2020) - Yang, Tianyu; Li, Li; Wu, Feng; Chen, Renjie
Abstract: The lithium metal anode is one of the most promising anodes for next‐generation high‐energy‐density batteries. However, the severe growth of Li dendrites and large volume expansion leads to rapid capacity decay and shortened lifetime, especially in high current density and high capacity. Herein, a soft 3D Au nanoparticles@graphene hybrid aerogel (AuGA) as a lithiophilic host for lithium metal anode is proposed. The large surface area and interconnected conductive pathways of the AuGA significantly decrease the local current density of the electrode, enabling uniform Li deposition. Furthermore, the 3D porous structure effectively accommodates the large volume expansion during Li plating/stripping, and the Li x Au alloy serves as a solid solution buffer layer to completely eliminate the Li nucleation over‐potential. Symmetric cells can stably cycle at 8 mA cm −2 for 8 mAh cm −2 and exhibit ultra‐long cycling: 1800 h at 2 mA cm −2 for 2 mAh cm −2, and 1200 h at 4 mA cm −2 for 4 mAh cm −2, with low over‐potential. Full cells assemble with a Cu@AuGALi anode and LiFePO4 cathode, can sustain a high rate of 8 C, and retain a high capacity of 59.6 mAh g −1 after 1100 cycles at 2 C. Abstract : A soft 3D Au nanoparticles@graphene hybrid aerogel (AuGA) is designed and fabricated. The porous structure with its large surface area significantly decreases the local current density and accommodates the large volume expansion during Li metal plating/stripping. High Coulombic efficiency, impressive symmetric cell performance, and full cells performance are simultaneously achieved under high current conditions.